Hydrocarbon Composition of Crude Oils from the Oldest Formation of the Punjab, Pakistan - Inayat, Asma; Khan, Shahid Rehman; Hamid, Abdul (Biological Sciences - PJSIR, 2007)
Four crude oils from the oldest formation of the Punjab basin were analyzed for the hydrocarbons . These crude oils belong to two sedimentary basi n s namely the Punjab Basin and Sindh Basi n. The samples were analyzed for chemical fossils usi ng a range of chemical methods and instrumenta l techniques. Quantification and characterization of i solated compoun ds were carried out usi ng data from the l i terature and referen ce compound. Gas chromatograms (GC) of the saturated h ydrocarbon fractions of crude oi l s were characterized by a striking series of peaks, el uti ng between th e -C 20 26 n-al kanes mai nl y i n the C range. Optim ized GC resolution showed that each peak is a co-el ution of subpeak wh ich corresponds to a complex series of monomethyla lkanes. The h ydrocarbon composition i n terms of depositional environment, l evels of maturation, and the nature of the pri mitive microorgan isms which existed d u ring ancient times were interpreted.